2021
DOI: 10.1051/0004-6361/202039706
|View full text |Cite
|
Sign up to set email alerts
|

How planets grow by pebble accretion

Abstract: During their formation, planets form large, hot atmospheres due to the ongoing accretion of solids. It has been customary to assume that all solids end up at the center, constituting a “core” of refractory materials, whereas the envelope remains metal-free. However, recent work, as well as observations by the Juno mission, indicate that the distinction may not be so clear cut. Indeed, small silicate, pebble-sized particles will sublimate in the atmosphere when they hit the sublimation temperature (T ~ 2000 K).… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 125 publications
(163 reference statements)
2
50
0
Order By: Relevance
“…During the buildup of the core, we set the fraction of matter that is accreted to the core (with mass M c ) at M < M iso to 90% of the total accreted matter (10% of accreted pebbles contribute to the primary envelope). This approach is supposed to account for pebble evaporation into the planetary envelope during core buildup in a simplified way compared to more sophisticated models (e.g., Brouwers & Ormel 2020;Ormel et al 2021), who actually show that even less than 50% of the solids accreted via pebbles make up the core and the evaporated pebbles make up most of the heavy element content of these forming planets (Ormel et al 2021). The initial growth during the core buildup in our model is thus simply described via Ṁcore = 0.9 Ṁpeb ; Ṁgas = 0.1 Ṁpeb ,…”
Section: Accretionmentioning
confidence: 99%
See 2 more Smart Citations
“…During the buildup of the core, we set the fraction of matter that is accreted to the core (with mass M c ) at M < M iso to 90% of the total accreted matter (10% of accreted pebbles contribute to the primary envelope). This approach is supposed to account for pebble evaporation into the planetary envelope during core buildup in a simplified way compared to more sophisticated models (e.g., Brouwers & Ormel 2020;Ormel et al 2021), who actually show that even less than 50% of the solids accreted via pebbles make up the core and the evaporated pebbles make up most of the heavy element content of these forming planets (Ormel et al 2021). The initial growth during the core buildup in our model is thus simply described via Ṁcore = 0.9 Ṁpeb ; Ṁgas = 0.1 Ṁpeb ,…”
Section: Accretionmentioning
confidence: 99%
“…We have assumed that during pebble accretion 90% of the accreted pebbles are attributed to the core and 10% are attributed to the heavy-element-rich atmosphere during core buildup. However, more detailed models have revealed that less than 50% of the accreted solids contribute to the core, while the remaining pebbles contribute to the high metallicity envelope (e.g., Brouwers & Ormel 2020;Ormel et al 2021). Taking a larger fraction of heavy elements to be accreted into the early atmosphere rather than the core will not influence the total heavy element content of the planet, because the accreted mass is the same.…”
Section: Interior Structurementioning
confidence: 99%
See 1 more Smart Citation
“…As volatile partitioning in the deep interior has been neglected for inference studies of exoplanets, previous interior predictions have thus far generally underestimated the amount of water and hydrogen for sub-Neptunes. Sub-Neptune envelopes may possess compositional gradients (Ormel et al 2021;Helled & Stevenson 2017), e.g., water might only be mixed within a hydrogen layer up to heights where water condenses. This effect itself influences the calculated radii and should ideally be considered in parallel with the partitioning of volatiles in the deeper planetary parts.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to circular planets, for which a well-defined pebble isolation mass is found even at large turbulent viscosities. This may have interesting implications for the formation of the cores of massive planets in highly turbulent protoplanetary discs, with the possibility of a eccentricity influences the pebble isolation mass 9 reduced efficiency of accretion for eccentric planets (Liu & Ormel 2018;Ormel et al 2021). It would be interesting to examine whether such planets could still accrete gas with their envelope contraction not being hindered by the accretion of solids.…”
Section: Discussionmentioning
confidence: 99%